Gambaran Penggunaan Obat Infeksi Saluran Pernapasan Akut (ISPA) pada Pasien Anak di Klinik X Kabupaten Tangerang Periode Januari-Maret 2025 - Wafa Wafa; Mochammad Hasan (An-Najat, 2025)
Acute Respiratory Tract Infection (ARI) remains one of the most common infectious diseases and a major public health concern in Indonesia. ARI is an infection that affects both the upper and lower respiratory tract, with symptoms ranging from mild to severe. This disease can occur across all age groups; however, data from the 2018 Basic Health Research (Riskesdas) revealed that the highest prevalence was found in children aged 1–4 years, accounting for 13.7%. The high incidence among young children highlights the importance of evaluating drug utilization patterns, particularly in relation to therapy choices and adherence to medical service standards. This study aimed to describe the pattern of drug use in pediatric patients diagnosed with ARI at Clinic X, Tangerang Regency. The variables observed included age group, sex, type of therapy, drug class, specific drugs prescribed, and dosage forms. This research employed a descriptive design with a retrospective approach, using data obtained from pediatric medical records. Samples were selected through probability sampling with a stratified random sampling technique, resulting in 185 eligible medical records. The findings indicated that pediatric ARI patients were predominantly within the age range of 0–5 years (54.6%), with a slightly higher proportion of males (51.9%). In terms of therapy, most patients received supportive treatment (71.9%). Regarding drug classification, antihistamines were the most frequently used (20.9%), with cetirizine being the most prescribed drug (20.8%). Powder formulations were the most common dosage form administered (48.8%), which may reflect the convenience of use in pediatric patients. Based on these results, it is recommended that the completeness of patient medical records be improved to ensure more accurate evaluation and clinical decision-making. Furthermore, strengthening adherence to medical service standards in the management of pediatric ARI is essential to ensure rational, effective, and safe drug therapy.